2021
DOI: 10.1111/jbg.12536
|View full text |Cite
|
Sign up to set email alerts
|

A selection signatures study among Middle Eastern and European sheep breeds

Abstract: Selection, both natural and artificial, leaves patterns on the genome during domestication of animals and leads to changes in allele frequencies among populations. Detecting genomic regions influenced by selection in livestock may assist in understanding the processes involved in genome evolution and discovering genomic regions related to traits of economic and ecological interests. In the current study, genetic diversity analyses were conducted on 34,206 quality‐filtered SNP positions from 450 individuals in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 102 publications
(125 reference statements)
0
10
0
Order By: Relevance
“…The genomes of local breeds have been under natural and artificial selection for centuries to transmit the desired properties to the descendants. These genetic changes shaped recent gene pools, and can be used for investigating genetic relatedness among breeds (Eydivandi et al, 2021a;Ju et al, 2019). Our study showed that the genomes of Iranian horse breeds contain multiple genomic regions under selective pressures (adaptation and/or breeding), representing an opportunity for a more detailed investigation the genes involved in these procedures.…”
Section: Selection Signaturementioning
confidence: 81%
“…The genomes of local breeds have been under natural and artificial selection for centuries to transmit the desired properties to the descendants. These genetic changes shaped recent gene pools, and can be used for investigating genetic relatedness among breeds (Eydivandi et al, 2021a;Ju et al, 2019). Our study showed that the genomes of Iranian horse breeds contain multiple genomic regions under selective pressures (adaptation and/or breeding), representing an opportunity for a more detailed investigation the genes involved in these procedures.…”
Section: Selection Signaturementioning
confidence: 81%
“…The genomes of local breeds have been under natural and artificial selection for centuries to transmit the desired properties to the descendants. These genetic changes shaped recent gene pools, and can be used for investigating the genetic relatedness among breeds (Eydivandi et al 2021a ; Ju et al 2019 ; Rajawat et al 2022 ). Our study showed that the genomes of Iranian horse breeds contain multiple genomic regions under selective pressures (adaptation and/or breeding), representing an opportunity for a more detailed investigation of the genes involved in these procedures.…”
Section: Discussionmentioning
confidence: 99%
“…Fst was a basic indicator for traditionally measuring genetic differentiation among populations. Understanding population structure and genetic background in an evolutionary context [13][14][15] . The corresponding gene loci and their functions were found by analyzing the selected regions with the Fst value in the top 1%.…”
Section: Fst Analysismentioning
confidence: 99%